Mechanisms of interventions targeting modifiable factors for dementia risk reduction - Matton, Anna; Stephen, Ruth; Daniilidou, Makrina; Barbera, Mariagnese; Alanko, Vilma; Ballin, Marcel; Ford, Jamie; Hemiö, Katri; Lehtisalo, Jenni; Rocha, Sabsil López; Mangialasche, Francesca; Ngandu, Tiia; et al. (Molecular neurodegeneration, 2025)
The global prevalence of dementia is increasing. With no widely available and accessible treatments to halt or reverse the progression of dementia, exploring preventative strategies is critical. Lifestyle-based interventions show promise in preventing or delaying dementia onset. However, understanding the complex and multifactorial mechanisms underlying dementia, and how interventions target these pathways, is essential for developing personalized and effective strategies. In this review, we examined the current evidence of the mediating pathways in dementia risk reduction. We focused on mechanisms investigated in single-domain interventions on physical exercise, cognitive training, diet, metabolic/cardiovascular or psycho-social risk factors in line with those combined in the landmark FINGER trial. Additionally, we synthesized existing literature on mechanisms of action in multimodal interventions combining multiple lifestyle changes. Most evidence was identified in relation to neuroimaging biomarkers with positive effects for all intervention components. The evidence among fluid biomarkers of Alzheimer’s disease and related disorders (ADRD) (amyloid-beta peptide (Aβ), tau and neurofilament light chain (Nfl)) vascular markers, inflammatory markers, and neurotrophins were less conclusive, though physical exercise consistently appeared to impact several of these pathways. The findings of this review underscore the potential of lifestyle-based interventions in modulating several different types of pathophysiological pathways associated with dementia. As the number of dementia cases reach epidemic proportions, a multifaceted approach is needed. We propose that the next critical step in dementia prevention/risk reduction is to refine existing intervention tools and develop an adaptive platform that integrates different lifestyle interventions tailored to individual risk profiles and needs. Understanding the underlying mechanisms and biomarkers related to modifiable risk factors will be instrumental to optimising these interventions.